Seasonal Variation in Chemical Composition of Size-Segregated Aerosols Over the Northeastern Arabian Sea - Kaushik, Ankush; Kumar, Ashwini; Aswini, M. A; Panda, P. P.; Shukla, Garima; Gupta, N. C. (Frontiers in Environmental Science, 2021)
Water-soluble species constitute a significant fraction (up to 60–70%) of the total aerosol loading in the marine atmospheric boundary layer (MABL). The “indirect” effects, that is, climate forcing due to modification of cloud properties depend on the water-soluble composition of aerosols. Thus, the characterization of aerosols over the MABL is of greater relevance. Here, we present 1-year long aerosol chemical composition data of PM10 and PM2.5 at a costal location in the northeastern Arabian Sea (Goa; 15.45°N, 73.20°E, 56 m above the sea level). Average water-soluble ionic concentration (sum of anion and cation) is highest (25.5 ± 6.9 and 19.6 ± 5.8 μg·m−3 for PM10 and PM2.5, respectively) during winter season and lowest during post-monsoon (17.3 ± 9.1 and 14.4 ± 8.1 μg·m−3 for PM10 and PM2.5, respectively). Among water-soluble ionic spices, SO42- ion was found to be dominant species in anions and NH4+ is dominant in cations, for both PM10 and PM2.5 during all the seasons. These observations clearly hint to the contribution from anthropogenic emission and significant secondary inorganic species formation. Sea-salt (calculated based on Na+ and Cl−) concentration shows significant temporal variability with highest contribution during summer seasons in both fractions. Sea-salt corrected Ca2+, an indicator of mineral dust is found mostly during summer months, particularly in PM10 samples, indicates contribution from mineral dust emissions from arid/semiarid regions located in the north/northwestern India and southwest Asia. These observations are corroborated with back-trajectory analyses, wherein air parcels were found to derive from the desert area in summer and Indo-Gangetic Plains (a hot spot for anthropogenic emissions) during winter. In addition, we also observe the presence of nss-K+ (sea-salt corrected), for PM2.5, particularly during winter months, indicating influence of biomass burning emissions. The impact on aerosol chemistry is further assessed based on chloride depletion. Chloride depletion is observed very significant during post-monsoon months (October and November), wherein more than 80 up to 100% depletion is found, mediated by excess sulfates highlighting the role of secondary species in atmospheric chemistry. Regional scale characterization of atmospheric aerosols is important for their better parameterization in chemical transport model and estimation of radiative forcing.